Evaluasi Potensi Biomassa untuk Co-Firing dengan Metode Proporsional Nilai Energi Tanaman Kaliandra dan Batubara pada PLTU Banko Barat - Bagus Totok Purnomo; Melania Suweni Muntini (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to evaluate the technical feasibility of energy-based biomass co-firing using Calliandra calothyrsus biomass at the Banko Barat 3 × 10 MW coal-fired power plant owned by PT Bukit Asam Tbk. The method employed involves fuel characterization through proximate and ultimate analyses of coal and biomass (woodchips and wood pellets). The Higher Heating Value (HHV) was estimated using the Dulong and Channiwala correlations. The energy-equivalent substitution ratio was determined by matching the HHV values, while biomass availability was assessed using a Geographic Information System (GIS)-based land analysis covering a cultivation area of 80 ha. The results indicate that replacing 1 kg of coal requires approximately 1.16 kg of woodchips or 1.17 kg of wood pellets. However, the available biomass supply can only support coal substitution at a limited level. In conclusion, energy-based biomass co-firing provides a more reliable framework than mass-based substitution for planning low-carbon energy transitions in coal-fired power plants, although biomass supply capacity remains a major constraint. Keywords: biomass co-firing, calliandra biomass, coal-fired power plant, energy-based substitution, HHV